Job satisfaction of foreign-educated nurses in Malaysia: A cross-sectional study - Lee, Su Yen; Soh, Kim Lam; Japar, Salimah; Ong, Swee Leong; Soh, Kim Geok; Tsujita, Yuko (Belitung Nursing Journal, 2021)
Background: The transition process of migration to work abroad can be challenging and, depending on how it is handled, can impact the job satisfaction level of these foreign-educated nurses. A clear understanding of migrant nurses’ job satisfaction is critical for effective translation of nursing practice across the health systems and cultures. Objective: This study examined the job satisfaction of the foreign-educated nurses in Malaysia, which includes the job satisfaction dimensions and the significant difference between sociodemographic status and job satisfaction. Methods: A cross-sectional survey of 102 foreign-educated nurses working in private hospitals, clinics, hemodialysis centers, nursing homes, and private homes in Malaysia was conducted from September 2017 to March 2018. Data were collected using a structured questionnaire. Descriptive statistics, Mann-Whitney U, and Kruskal Wallis tests were used to analyze the data.   Results: The study revealed that the participants had a median satisfaction score of 22 (IQR = 19 to 24). Serving the sick and needy and participants’ self-respect were the highest satisfaction dimensions among the participants (Median = 3, IQR = 3 to 3). Moreover, the job satisfaction was significantly higher for registered foreign-educated nurses (mean rank = 62.5) than for unregistered foreign-educated nurses(mean rank = 48.65) when working in other countries (p = 0.02). Indian nurses (mean rank = 60.36) also expressed higher satisfaction in terms of working in other countries than Filipino nurses (mean rank = 46.88; p = 0.02). In addition, positive relationships with colleagues and superiors led to higher satisfaction among Indian nurses (mean rank = 61.02) than among Filipino nurses (mean rank = 47.24; p = 0.04). The job satisfaction of male foreign-educated nurses was significantly higher than their female counterparts in terms of self-respect, relationship with fellow nurses and superiors, working in other countries, career development, and ease of finding employment (p < 0.05). Conclusion: The overall job satisfaction among the foreign-educated nurses in Malaysia is high, mainly when serving the sick and needy, and their degree of self-respect. Understanding job satisfaction among foreign-educated nurses in Malaysia enables the management team to develop effective strategies for addressing nursing shortages and improving the quality of patient care.